2017
DOI: 10.1186/s13256-017-1367-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic device-assisted knee extension training during the early postoperative period after opening wedge high tibial osteotomy: a case report

Abstract: BackgroundMaintenance or restoration of a good range of motion of the knee is one of the most important outcomes following knee surgery. According to previous studies, opening wedge high tibial osteotomy enables better recovery of range of motion in knee flexion than that achievable after total knee arthroplasty or unicompartmental knee arthroplasty. However, few reports provide a detailed description of the postoperative recovery of knee extension range of motion after opening wedge high tibial osteotomy. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Moreover, the use of robot-assisted training significantly decreased the pain level during active movement and improved performance compared with conventional therapy [ 10 ]. The robot-assisted training improved the neuromuscular functions of the quadriceps, which allowed the knee to extend fully and did not increase the level of knee pain immediately after surgery [ 23 ]. Improvements in isometric strengths after RAGT in the hip, knee, and ankle were similar to the measurements after conventional strengthening program [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of robot-assisted training significantly decreased the pain level during active movement and improved performance compared with conventional therapy [ 10 ]. The robot-assisted training improved the neuromuscular functions of the quadriceps, which allowed the knee to extend fully and did not increase the level of knee pain immediately after surgery [ 23 ]. Improvements in isometric strengths after RAGT in the hip, knee, and ankle were similar to the measurements after conventional strengthening program [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…2A, B). The patient was then instructed to perform knee extension and flexion thereby contracting his quadriceps and hamstring muscles 5) . Generally, several anatomical problems occur following ACLR: slightly lax graft tension, partial graft tear, poor synovial coverage, and cyclops-like lesion 7) .…”
Section: Participant and Methodsmentioning
confidence: 99%
“… ). The patient was then instructed to perform knee extension and flexion thereby contracting his quadriceps and hamstring muscles 5 ) .…”
Section: Participant and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported on the feasibility and efficacy of HAL training in the rehabilitation of patients with impaired walking due to chronic multifactorial conditions 6 and to various underlying conditions, including musculoskeletal ambulation disorder, 7 spinal cord injury, [8][9][10][11][12][13][14] stroke, [15][16][17][18][19][20][21][22] knee joint disease, [23][24][25][26] and brachial plexus injury. 27,28 However, the applicability of HAL training in patients with OPLL has only been evaluated in a few case reports to date.…”
Section: Introductionmentioning
confidence: 99%